UPAYA PENINGKATAN KAPASITAS UMKM MELALUI PENERAPAN SOCIAL MEDIA MARKETING - Suharyati Suharyati; Ediwarman Ediwarman; Tati Handayani (Gapenas Publisher, 2021)
The global pandemic of covid disease, covid-19, has caused the world's economic growth and Indonesia's to decline. The positive impact of the Covid-19 pandemic is that it encourages all business actors to fight for the survival of their companies. The rapid advancement of technology can be used to market MSME products to various corners of consumers online. Improving the quality of human resources and information technology is necessary to adapt to various technologies that have emerged in the era of the industrial revolution 4.0. Community service activities with the theme